The developmental orgins of Tracheo-oesophageal malformations : investigating the molecular and morphological basis of foregut abnormalities in Adriamycin treated mice and in newly established 3D foregut culture system - Mc Laughlin, Danielle (Trinity College (Dublin, Ireland). Department of Zoology, 2015)
Oesophageal Atresia/Tracheo-oesophageal fistula (OA/TOF) is a congenital malformation that requires urgent and complex surgery soon after birth and is associated with life-long respiratory and gastro-intestinal morbidity. Although genetic aetiology has been identified for some syndromic forms, in the majority of cases the cause of this important clinical condition remains unknown.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin